Impact of doctor-shopping behavior on patient survival in lung cancer: findings from a 11-year cohort study using Korean claims data - Minwoo Hong; Il Yun; Jong Youn Moon (BMC Cancer)
Abstract Background This population-based cohort study aimed to explore the impact of doctor-shopping behavior (DSB) on the survival of new patients with lung cancer in Korea to make policy suggestions for the efficient use of medical care for cancer patients. Methods The cancer cohort data used in this study were obtained from the Korean National Health Insurance Service database, which contains claim records for all cancer patients in Korea between 2009 and 2021. After setting the washout period and exclusion criteria, 280,030 patients were found to be eligible for the analysis. The outcome variables were death within 30 days, 90 days, 1 year, and survival over 5 years after the first diagnosis. DSB, a variable of interest, was defined as the number of visits from the first diagnosis to the first treatment, and was classified into four quartiles. A multiple logistic regression model was used to examine the effects of DSB on the survival of patients with lung cancer. Results Compared to patients who visited the doctor less than once (Q1), those with 2–9 visits (Q2, Q3) had a lower likelihood of death within 30 days, 90 days, and 1 year, and a higher probability of survival over 5 years. However, patients with more than 10 visits (Q4) had significantly increased odds of death. Moreover, those with excessive doctor shopping had about a 12% decrease in the likelihood of surviving beyond 5 years compared to those with minimal visits (95% CI: 0.85–0.92). Stratified analysis revealed that, especially when patients who are middle class or higher living in metropolitan cities engage in excessive doctor shopping, the likelihood of death within 1 year increases by 14–18%, and the survival rate over 5 years decreases by 12–18%, compared to those who rarely doctor shopped. Conclusion For patients with lung cancer, moderate doctor shopping can positively affect survival, while excessive visits can increase mortality. This effect was more notable among patients with middle or higher incomes and those living in metropolitan cities. These results highlight the need for policies that regulate the use of medical resources, especially among patients with greater access to medical care, to ensure the efficient utilization of medical care for improved health outcomes.